Non-Western Perspectives on Human Communication : Implications for Theory and Practice. - Kim, Dr. Min-Sun (SAGE Publications, 2002)
What it means to be a self - and a self communicating and being in a particular culture - are key issues interwoven throughout Min-Sun Kim's impressive text, Non-Western Perspectives on Human Communication. Going beyond cultural descriptions or instructions on adapting to specific cultures, the author interrogates the very core assumptions underlying the study of human communication and challenges longstanding individualistic, Western models on which much intercultural research is based. Kim proposes a non-western way of conceptualizing identity, or the "self"--The cornerstone of cultural re.